#### Answer

$\frac{-5}{12}$

#### Work Step by Step

$\frac{2}{6}$-$\frac{3}{4}$=$\frac{2*2}{6*2}$-$\frac{3*3}{4*3}$=
$\frac{4}{12}$-$\frac{9}{12}$=$\frac{4-9}{12}$=$\frac{-5}{12}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$\frac{-5}{12}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.